Home buyers’ perception on abandoned housing projects in Malaysia - Abdul Razak, Dzuljastri; Abu Samah, Zariah; Abdul Wahab, Abdul Hamid (Zes Rokman Resources, 2016)
Abandoned housing project has become a major issue in the housing industry in Malaysia. Despite several efforts by the government to curb the problem, it still exists in the country. The present study offers new insights on the perception of home buyers concerning abandoned housing projects in Malaysia. Two Islamic home financing products which include Bai Bithaman Ajil (BBA) and Musharakah Mutanaqisah Partnership (MMP) are considered. The objective is to determine, based on the opinion of the respondents, which of these two products is more preferred and what are some of the potential causes of abandoned housing projects in Malaysia. The perception of home buyers is evaluated based on five main categories of items which include, financing concepts used, justice and fairness, pricing methods, legal and governance, and shari’ah compliance issues. The findings show that, using MMP concept in Islamic home financing is preferred as compared to BBA. Also, the insufficient laws and regulations as well as the use of BBA financing are viewed as some of the possible contributing factors to the problem of abandoned housing projects in Malaysia.